Indicator Conformity Analysis of State Programs (Housing and Sports Development) at Federal and Regional Levels - Yu. V. Gerasimova (Управленческие науки)
The article verifies the consistency between strategic documents at the federal and the regional levels on the two subjects of joint jurisdiction of theRussian Federationand the constituent entities of theRussian Federation: providing citizens with housing and development of sports. The federal law on strategic planning provides for the coordination of target values of indicators of strategic documents on joint management. Provisions on the need for such coordination in 2016–2017 appeared in the bylaws on the formation of state programs and strategies for socio-economic development. However, according to the research, the target values of the main indicators of these sectors of the economy as of the beginning of2018 inthe policy documents stated to be not coordinated — their values, established in federal state programs, are 10–20% higher than the aggregate values declared by the subjects of the russian federation in regional state programs. The study was conducted on the basis of a comparison of the data of strategic documents of the federal and regional levels. The main attention is paid to studying the coherence of state programs as the most relevant strategic documents related to the budget process. The author analyzes the sets of target indicators used by federal and regional government programs to establish medium-term goals. In the course of the research several indicators were identified for each direction, for which a more detailed analysis of the sequence of federal and aggregated regional values was carried out. In the direction of housing analysis the number of housing in 2020 was investigated, and in the direction of development of physical culture and sports the following indicators were review: the proportion of the population systematically engaged in physical culture and sports in 2020; share of the population provided with sports facilities on the basis of one-time visitor capacity in 2020. Statistical methods were used in the study. The author comes to the conclusion that in order to ensure the consistency of the indicators of strategic documents, it is necessary to select the key indicators for each subject of joint management, and to develop principles for their coordination as well as to create a mechanism for harmonizing indicators.